DESIGN OF A VIRTUAL CONTROL STSTION FOR DISTURBANCES THAT AFFECT TEMPERATURE IN INDUTRIAL PROCESS - Poma Deza, Jorge (2007)
The article presents the development of a virtual ststion using LabVIEW, instrumentation virtual software made by National Instruments, software of virtual instrumentation, which allows monitoring and to supervise variables in real time in an industrial process. This system provides one interface graph of virtual control, considering the heat needed for the process in funtioning, nevertheless, the interferences generated towards the process can achieve an increase of the temperature to the system, incorporating an alarm to avoid losses in the production. Finally, option of sampling have been designed in the Control Panel, as quantity of information to measure, passes time, speed of sampling, quantity of taken information, to indicate the time in which some event has happened, etc. Important to facilitate the capture of decisions.